PERANCANGAN VIDEO IKLAN PROMOSI DI PERUSAHAAN KAOS MENGGUNAKAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE: DESIGN OF PROMOTIONAL VIDEO ADVERTISING IN T-shirt COMPANIES USING MULTIMEDIA DEVELOPMENT LIFE CYCLE METHOD - Okta Veza; Eka Safira (Engineering and Technology International Journal, 2020)
The design of this promotional video advertisement was made to introduce the company's products to potential buyers, find information about clothing products and typical Batam souvenirs, and can be a means of company promotion. The design is targeted to increase the buying interest of potential consumers. The design of a promotional video ad is based on a case study at Graha T-Obenk Premium Kaos Batam which is a 3 (three) month process. The object of the activities carried out is in the form of direct observations in the field to see the circumstances and situations that occur, how the marketing process has been done to consumers so far. From the conditions that occur in the field, we can see the lack of interest from potential consumers to offers in the form of catalogs in the form of brochures and books. The conclusions and suggestions in this promotional video advertisement are to increase the attractiveness of potential consumers in finding information about Batam souvenir products and also to increase company promotions.